Clinical outcomes of micropulse transscleral cyclophotocoagulation: 2 years of experience in Portuguese eyes - Basto, R. C.; Almeida, J.; Roque, J. N.; Henriques, S.; Gonçalves, A. S.; Vaz, F. T.; Carvalho, H.; Prieto, I. (Journal of Current Glaucoma Practice, 2023)
Aim: This study evaluates the safety and efficacy of micropulse transscleral cyclophotocoagulation (MPTSCPC) in glaucoma patients, with standard parameters, over a 24-month period. Methods: Retrospective analysis of 61 eyes undergoing MPTSCPC from January 2018 to December 2020 was carried out. Patients received 160 seconds of laser, with settings of 2000 mW/cm2 and a duty cycle of 31.3%. Results: A total of 61 eyes were included, arranged in an age distribution of 73.9 ± 10.8 years. The most frequent diagnosis was primary open-angle glaucoma (POAG), with a mean best-corrected visual acuity (BCVA) of 5/10 in the Snellen Visual chart. Around 37.7% of the eyes had undergone at least one glaucoma filtration surgery prior to MPTSCPC. The mean pretreatment intraocular pressure (IOP) was 24.9 ± 8.6 mm Hg. Except for the contrast at 24 months, at every other follow-up visit, there was a significant reduction (p ≤ 0.001) in IOP and in the number of topical drugs required to control IOP, from four (baseline) to three, with oral acetazolamide suspension in most cases. The total success rate (absolute and clinical successes combined) was 81.9% after 1 year of the treatment. There was no drop in visual acuity or cases of serious complications. There is a positive and significant correlation between prior glaucoma surgery and the need for reinterventions (p = 0.028). Conclusions: Micropulse transscleral cyclophotocoagulation (MPTSCPC) is an effective and safe procedure for reducing IOP within a broad spectrum of glaucoma patients. Additional studies are needed to confirm the current indications, widen their scope, and determine the optimal treatment settings on an individual basis.